Design Rules for Actuators in Active Mechanical Systems - Gomis-Bellmunt, Oriol (Springer, 2012)
In active mechanical systems (mechanisms or structures) the possibility of a coupling between active and passive elements at an early stage of the design process is becoming more and more significant.